EFFECTS OF DIETARY STARCH LEVELS WITH HIGH AND LOW FORAGE NEUTRAL DETERGENT FIBER IN DAIRY BUFFALOES - Sundas Qamar; Muhammad Naveed ul Haque; Hifzulrahman; Muhammad Asim Tausif; Ehsan Ullah Khan; Hina Tahir; Ijaz Hussain; Saba Anwar; Muhammad Saadullah; Saima Naveed (Journal of Animal and Plant Sciences, 2025)
The aim of the experiment was to determine the effects of starch, neutral detergent fiber from forage (FNDF) levels and their interaction on milk yield, milk composition, methane production, and blood metabolites in lactating buffaloes. Sixteen multiparous Nili Ravi buffaloes (averaging 9 ± 1.58 kg/d of milk yield, 5.00 ± 1.61% of milk fat, 534 ± 83 kg of BW, and 46 ± 20 DIM, mean ± SD at the start of the study) were enrolled and received 4 treatments with 2 different levels of FNDF according to a changeover design with 6-wk periods under restricted feed intake. Within each FNDF supply level, the buffaloes received 2 different starch levels of concentrate with 3-wk subperiods. Corresponding to the following treatments: (1) 39% FNDF and 33% starch, (2) 39% FNDF and 49 % starch, (3) 50% FNDF and 33% starch, and (4) 50% FNDF and 49% starch. Milk production was increased by 4.27%, when low FNDF was fed compared with high forage NDF. Milk fat and lactose yields were increased by 7.50, 14.6%, respectively, in low FNDF. Energy- corrected milk (ECM) was increased by 5.09% in low FNDF diets than high forage NDF. Predicted enteric methane intensity decreased with high starch and low FNDF level. It is concluded that milk production, milk fat, and lactose yield increased in early lactating buffaloes fed low FNDF compared to high FNDF. Production efficiencies also improved with the low FNDF diet. However, interaction between FNDF and starch levels was observed for the parameters investigated.
Keywords: Buffalo; Forage neutral detergent fiber; Milk yield; Nili Ravi; Starch